Effect of HfO2 on the compatibility of borosilicate sealing glasses for solid oxide fuel cells application. Issue 77 (22nd August 2015) - Liu, Honglin; Zhao, Dandan; Chen, Shunrun; Huang, Jinwan; Tang, Dian; Zhang, Teng
<x xml:space="preserve">Abstract</x> HfO2 condenses the glass structure, blocks the interdiffusion between glasses and Cr-containing interconnects, and thus reduces the detrimental interfacial reaction.